Isolasi dan Identifikasi Jamur Penyebab Onikomikosis pada Petani di Kabupaten Sukoharjo Jawa Tengah - Prabandari, Anggraeni Sih; Pramonodjati, Fredericus; Sari, Ajeng Novita; Cahyaningtias, Agatha Dinda Ayu (Indonesian Journal on Medical Science, 2024)
Farmers are susceptible to dermatophyte infection because of their daily contact with the soil which is the habitat of mold. Onychomycosis (tinea unguium) is a disease of the nails and toenails caused by dermatophytes. Although it does not cause death, this disease can reduce the productivity of sufferers. Personal hygiene, the use of personal protective equipment and the long time of being a farmer, are closely related to the incidence of Onychomycosis. This study aims to determine the species of mold that causes onychomycosis. This type of research is descriptive with a cross sectional approach. The respondents of the study amounted to 24 rice farmers in Mayang Village, Gatak District, Sukoharjo Regency. Data in this study were obtained from interviews, observations and nail examinations. Onychomycosis is seen based on changes in structure and color in the fingernails and toenails. The infected nail is removed and examined microscopically. The specimen was then cultured on Saboraoud Dextrose Agar (SDA) media. Growing colonies are identified macroscopically by looking at the morphology and characteristics of the colony and examined microscopically by staining Lactophenol Cotton Blue (LCBP). The results of the study found two types of dermatophyte and non-dermatophyte fungi. Onychomycosis infection is dominated by dermatophyte fungi with a prevalence of 63% (15/24), while the rate of non-dermatophyte fungal infection is 37% (9/24). Dermatophyte species that infected Trichopyton rubrum (33%) and Trichopyton mentagophytes (29%). While non-dermatophyte fungi found are Aspergilus fumigatus (17%) and Aspergilus niger (21%).